NiCoMn LDH electrode material rich in oxygen vacancies as well as preparation method and application of NiCoMn LDH electrode material
By growing Co-ZIF-L arrays on foam nickel and introducing oxygen vacancies, NiCoMn LDH electrode materials with oxygen vacancies were prepared, which solved the problem of insufficient conductivity and cyclic stability of existing LDH materials, and achieved high Specific capacitance and good rate performance.
Patent Information
- Application Number
- CN202411767476.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing LDH electrode materials have problems with poor cyclic stability and conductivity, and it is difficult to achieve synergistic effects between polymetal cations and oxygen vacancies at the same time.
Using a simple and low-cost preparation method, by growing a zeolite imidazole skeleton Co-ZIF-L array on foam nickel, and etching through manganese and nickel bimetallic, then introducing oxygen vacancies into NiCoMn LDH, through Immersion of hydrogen oxide solution.
The electrochemical performance was significantly improved, including specific capacitance and cyclic stability, and Vo-NiCoMn LDH showed a high specific capacitance of 3116.18F/g and a rate performance of 85.84% in 2M KOH electrolyte solution.
Smart Images

Figure CN119430321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrode material preparation methods and battery technology, and specifically relates to a NiCoMn LDH electrode material rich in oxygen vacancies, a preparation method and an application thereof. Background Art
[0002] Aqueous alkaline batteries are a promising rechargeable energy device that has attracted attention due to their high ionic conductivity, high power density, etc. Synthesis of electrode materials with high specific capacity and stability through simple, safe, and environmentally friendly methods is a current research hotspot.
[0003] Layered double hydroxides (LDHs) are considered promising cathode materials due to their high redox activity, environmentally friendly properties, and unique interlayer embedding properties. However, most LDHs have problems with cycle stability and poor conductivity. To this end, on the one hand, the electronic configuration can be adjusted by doping metal atoms to improve the electrochemical activity; on the other hand, oxygen vacancy defects can be incorporated into LDH to adjust the electronic structure to promote electrochemical charge transfer, thereby improving the conductivity and electrochemical stability of the material. The addition of oxygen vacancies not only does not affect the layered structure of LDH, but also increases the concentration of active centers, thereby accelerating electron transfer and ion conversion. However, LDHs with both multi-metal cations and oxygen vacancies are still difficult to achieve. Summary of the invention
[0004] In order to solve the above technical problems, the present invention adopts a simple and low-cost preparation method to achieve the preparation of NiCoMn LDH electrode material rich in oxygen vacancies. The NiCoMn LDH electrode material rich in oxygen vacancies obtained by this method has the advantage of significantly improving electrochemical performance.
[0005] The present invention provides a method for preparing a NiCoMn LDH electrode material rich in oxygen vacancies, comprising the following steps:
[0006] (1) 2-Methylimidazole and cobalt salt were dissolved in solvents to form solution A and solution B, respectively. Then a pretreated nickel foam (3×4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand, washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain a Co-ZIF-L precursor;
[0007] (2) adding nickel salt and manganese salt into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, adding the Co-ZIF-L precursor obtained in step (1), and performing a hydrothermal reaction to obtain NiCoMn LDH;
[0008] (3) The NiCoMn LDH prepared in step (2) is immersed in 20 mL of hydrogen peroxide solution. After the reaction, the sample is washed with distilled water for several times and dried in an oven at 60° C. for 24 h to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH.
[0009] In the step (1), the type of cobalt salt is not limited, including cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, etc., but cobalt nitrate hexahydrate is most preferred.
[0010] In the step (1), 2-methylimidazole and cobalt salt are completely dissolved in a solvent, and the type of solvent is not limited, including organic solvents and deionized water. The organic solvent includes but is not limited to one or more of methanol, ethanol, and DMF.
[0011] In the step (1), 2-methylimidazole and the cobalt salt are completely dissolved in the solvent, the molar concentration of 2-methylimidazole is preferably 0.25-0.55 mol / L, and the molar concentration of the cobalt salt is preferably 0.025-0.25 mol / L; the molar ratio of 2-methylimidazole to the cobalt salt is preferably 4:1.
[0012] In step (2), the type of manganese salt is not limited, including manganese chloride, manganese nitrate, manganese sulfate, manganese acetate, etc., but manganese chloride tetrahydrate is most preferred.
[0013] In step (2), the type of nickel salt is not limited, including nickel nitrate, nickel chloride, nickel acetate, etc., but nickel nitrate hexahydrate is most preferred.
[0014] In the step (2), the temperature of the hydrothermal reaction is 75-125°C, and most preferably 90°C; the time of the hydrothermal reaction is 0.5-2.5h, and most preferably 1h.
[0015] In the step (3), the NiCoMn LDH is immersed in a hydrogen peroxide solution, the volume concentration of the hydrogen peroxide solution is preferably 5%, and the immersion time is 0.5-3 hours, and most preferably 1 hour.
[0016] In summary, the NiCoMn LDH electrode material rich in oxygen vacancies of the present invention has the following characteristics:
[0017] Beneficial effects:
[0018] (1) Using nickel foam as the substrate material, a zeolite imidazole skeleton Co-ZIF-L array is grown on it, and manganese and nickel bimetallic etching is used, which not only retains the advantages of the ZIF material such as porous morphology and multiple active sites, but also enhances the synergistic effect between the three ions of manganese, nickel and cobalt, thereby improving the specific capacitance and cycle stability of the material. The NiCoMn LDH electrode material rich in oxygen vacancies prepared by the present invention increases oxygen vacancies through hydrogen peroxide oxidation, adjusts the electronic structure to promote electrochemical charge transfer, increases active sites, reduces the Gibbs free energy of the surface reaction, and thus reduces the energy barrier required for the redox reaction of the electrode material. High specific capacitance and rate performance are demonstrated in electrochemical tests. In a 2M KOH electrolyte solution, at a current density of 1A / g, the electrode material has a high specific capacitance of 3116.18F / g and a rate performance of 85.84% at a current density of 1A / g.
[0019] (2) The preparation method of the present invention is simple and effective, and the construction of the NiCoMn LDH electrode material rich in oxygen vacancies can be simply extended to construct other electrode materials with vacancy modification or MOF as sacrificial template for energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of Co-ZIF-L prepared in step (1) of Example 1 of the present invention;
[0021] Figure 2 This is a scanning electron microscope image of the NiCoMn LDH prepared in step (2) of Example 1 of the present invention;
[0022] Figure 3 This is a scanning electron microscope image of the Vo-NiCoMn LDH prepared in step (3) of Example 1 of the present invention;
[0023] Figure 4 The X-ray diffraction pattern of the Vo-NiCoMn LDH prepared in step (3) of Example 1 of the present invention is compared with the standard card;
[0024] Figure 5 The cyclic voltammetry curves of Vo-NiCoMn LDH prepared in step (3) of Example 1 of the present invention in 2M KOH electrolyte solution at different scan rates;
[0025] Figure 6 The chronoamperometric analysis diagram of the Vo-NiCoMn LDH prepared in step (3) of Example 1 of the present invention in a 2M KOH electrolyte solution at different current densities;
[0026] Figure 7The specific capacitance of the NiCoMn LDH prepared in step (2) of Example 1 of the present invention and the Vo-NiCoMn LDH prepared in step (3) as electrode materials in 2M KOH electrolyte solution. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are described in further detail below with reference to the accompanying drawings and examples.
[0028] Example 1
[0029] A method for preparing a NiCoMn LDH electrode material rich in oxygen vacancies comprises the following steps:
[0030] (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a piece of pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to allow it to be fully soaked, then solution B together with nickel foam was quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain a Co-ZIF-L precursor; the scanning electron microscope image of the prepared Co-ZIF-L is shown in Figure 1 As shown, nanosheets with smooth surface and uniform size are presented;
[0031] (2) 1.455 g of nickel nitrate hexahydrate and 0.989 g of manganese chloride tetrahydrate were added to 50 mL of deionized water, stirred until completely dissolved, and then transferred to a reactor. The Co-ZIF-L precursor prepared in step (1) was placed in the reactor and subjected to a hydrothermal reaction at 90° C. for 1 h. After the reaction, the precursor was washed and dried to obtain NiCoMn LDH. The scanning electron microscope image of the prepared NiCoMn LDH is shown in FIG. Figure 2 As shown in Figure 2, small nanosheets are assembled on the surface of large nanosheets. The X-ray diffraction pattern of NiCoMn LDH prepared by the above steps is shown in Figure 2. Figure 4 As shown; the diffraction peaks are all attributed to α-Ni(OH)2 (JCPDS No.38-0715);
[0032] (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 5% hydrogen peroxide solution and soaked for 1 hour. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60°C for 24 hours to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH. The scanning electron microscope image of the prepared Vo-NiCoMn LDH is shown in FIG. Figure 3 As shown, small nanosheets are assembled on the surface of large nanosheets.
[0033] The X-ray diffraction pattern of Vo-NiCoMn LDH prepared in the above steps is as follows: Figure 4 As shown; the diffraction peaks are all attributed to α-Ni(OH)2 (JCPDS No.38-0715).
[0034] The Vo-NiCoMn LDH prepared in the above steps was used as an electrode material for aqueous alkaline batteries, and its electrochemical performance was tested in a 2M KOH electrolyte solution. Figure 5 Cyclic voltammetry curves at different scan rates. Figure 6 Chronoamperometry diagrams at different current densities.
[0035] The Vo-NiCoMn LDH prepared in the above steps and the NiCoMn LDH prepared in step (2) were used as positive electrode materials for aqueous alkaline batteries, and their specific capacitances at different current densities were tested in a 2M KOH electrolyte solution. Figure 7 As shown, NiCoMn LDH and Vo-NiCoMn LDH have specific capacitances of 2336.7F / g and 3116.18F / g at 1A / g, respectively, indicating that the electrochemical performance is greatly improved by creating oxygen vacancies and constructing defects on the trimetallic LDH. At a current density of 10A / g, the rate performance of the Vo-NiCoMn LDH electrode material is 85.84%.
[0036] Example 2
[0037] (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a piece of pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain Co-ZIF-L precursor;
[0038] (2) adding 1.455 g of nickel nitrate hexahydrate and 0.989 g of manganese chloride tetrahydrate into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, then placing the Co-ZIF-L precursor obtained in step (1) in the reactor, and subjecting it to a hydrothermal reaction at 100 ° C. for 2.5 h. After the reaction, washing and drying are performed to obtain NiCoMn LDH;
[0039] (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 5% hydrogen peroxide solution and soaked for 1 hour. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60° C. for 24 hours to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH.
[0040] The prepared Vo-NiCoMn LDH was used as the positive electrode material of aqueous alkaline batteries, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a high specific capacitance of 2536.3F / g at 1A / g. At a current density of 10A / g, the rate performance of Vo-NiCoMn LDH was 83.3%.
[0041] Example 3
[0042] (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a piece of pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain Co-ZIF-L precursor;
[0043] (2) adding 0.75 g of nickel nitrate hexahydrate and 0.989 g of manganese chloride tetrahydrate into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, and then placing the Co-ZIF-L precursor prepared in step (1) in the reactor, and hydrothermally reacting at 90° C. for 1 h, washing and drying after the reaction to obtain NiCoMn LDH;
[0044] (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 5% hydrogen peroxide solution and soaked for 1 hour. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60° C. for 24 hours to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH.
[0045] The prepared Vo-NiCoMn LDH was used as an electrode material for aqueous alkaline batteries, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a high specific capacitance of 2418F / g at 1A / g. At a current density of 10A / g, the rate performance of Vo-NiCoMn LDH was 77.9%.
[0046] Example 4
[0047] (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a piece of pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain Co-ZIF-L precursor;
[0048] (2) adding 1.455 g of nickel nitrate hexahydrate and 1.552 g of manganese chloride tetrahydrate into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, and then placing the Co-ZIF-L precursor obtained in step (1) in the reactor, and subjecting the precursor to a hydrothermal reaction at 90° C. for 1 h, and washing and drying the mixture after the reaction to obtain NiCoMn LDH;
[0049] (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 5% hydrogen peroxide solution and soaked for 1 hour. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60° C. for 24 hours to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH.
[0050] The prepared Vo-NiCoMn LDH was used as an electrode material for aqueous alkaline batteries, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a high specific capacitance of 2093.2 F / g at 1 A / g. At a current density of 10 A / g, the rate performance of Vo-NiCoMn LDH was 74.5%.
[0051] Example 5
[0052] (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a piece of pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain Co-ZIF-L precursor;
[0053] (2) adding 1.455 g of nickel nitrate hexahydrate and 0.989 g of manganese chloride tetrahydrate into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, and then placing the Co-ZIF-L precursor prepared in step (1) in the reactor, and subjecting the precursor to a hydrothermal reaction at 90° C. for 1 h, and washing and drying the mixture after the reaction to obtain NiCoMn LDH;
[0054] (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 10% hydrogen peroxide solution and soaked for 3 h. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60° C. for 24 h to obtain a NiCoMn LDH electrode material rich in oxygen vacancies, referred to as Vo-NiCoMn LDH.
[0055] The prepared Vo-NiCoMn LDH was used as an electrode material for aqueous alkaline batteries, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a high specific capacitance of 2525F / g at 1A / g. At a current density of 10A / g, the rate performance of Vo-NiCoMn LDH was 81%.
[0056] The embodiments described above are detailed descriptions of the technical solutions of the present invention, which should be understood as specific implementation measures of the present invention and are not used to summarize the present invention. Any modifications, supplements or similar replacements made within the scope of the principles of the present invention shall fall within the scope of protection that the present invention should enjoy.
Claims
1. A method for preparing a NiCoMn LDH electrode material rich in oxygen vacancies, characterized in that: The preparation method comprises the following steps: (1) 0.985 g of 2-methylimidazole and 0.435 g of cobalt nitrate hexahydrate were dissolved in 30 mL of deionized water to form solution A and solution B, respectively. Then a pretreated nickel foam (3 × 4 cm 2 ) was placed in solution B to fully soak it, then solution B and nickel foam were quickly added to solution A, stirred vigorously for 2 minutes, allowed to stand for 4 hours, and washed with deionized water and ethanol respectively after the reaction, and vacuum dried at 60°C for 24 hours to obtain Co-ZIF-L precursor; (2) adding 1.455 g of nickel nitrate hexahydrate and 0.989 g of manganese chloride tetrahydrate into 50 mL of deionized water, stirring until completely dissolved, and then transferring to a reactor, and then placing the Co-ZIF-L precursor prepared in step (1) in the reactor, and subjecting the precursor to a hydrothermal reaction at 90° C. for 1 h, and washing and drying the mixture after the reaction to obtain NiCoMn LDH; (3) The NiCoMn LDH prepared in step (2) was placed in 20 mL of a 5% hydrogen peroxide solution and soaked for 1 hour. After the reaction, the sample was washed with distilled water several times and dried in an oven at 60° C. for 24 hours to obtain a NiCoMn LDH electrode material rich in oxygen vacancies.
2. Use of the NiCoMn LDH electrode material rich in oxygen vacancies prepared by the preparation method according to claim 1 as a positive electrode material for aqueous alkaline batteries.
